2016
DOI: 10.3109/02770903.2015.1108438
|View full text |Cite
|
Sign up to set email alerts
|

Burden of asthma among inner-city children from Southern Brazil

Abstract: The burden of asthma in Brazilian children seems to be substantial. New international guidelines with a special focus in developing countries settings, with more pragmatic approaches, should be a priority for discussion and implementation actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 27 publications
1
25
1
7
Order By: Relevance
“…These results are in line with recent guidelines [6,10], which reinforce the importance of ensuring access to medications for asthma control to high-risk population [11]. Importantly, asthma also constitutes a major cause of hospitalization in several Brazilian cities, with social level and intra-urban differences playing a role on the incidence of hospitalizations [12,13]. Moreover, the impact of free medications to treat asthma could be seen as an important mechanism to prevent deaths related to disease, since the population with higher risk to die by asthma complications are hospitalized patients [14,15].…”
Section: Discussionsupporting
confidence: 87%
“…These results are in line with recent guidelines [6,10], which reinforce the importance of ensuring access to medications for asthma control to high-risk population [11]. Importantly, asthma also constitutes a major cause of hospitalization in several Brazilian cities, with social level and intra-urban differences playing a role on the incidence of hospitalizations [12,13]. Moreover, the impact of free medications to treat asthma could be seen as an important mechanism to prevent deaths related to disease, since the population with higher risk to die by asthma complications are hospitalized patients [14,15].…”
Section: Discussionsupporting
confidence: 87%
“…It is important to note that some of our patients, prior to omalizumab treatment, had a history of >5 hospitalizations per year, and most patients exhibited uncontrolled disease even between exacerbations (data not shown). Most of our patients were sedentary, experienced high school absenteeism, and had frequent exacerbations . Therefore, omalizumab is currently the best therapeutic alternative that positively influences the quality of life of children with atopic STRA.…”
Section: Discussionmentioning
confidence: 92%
“…We have shown that omalizumab significantly decreased the number of hospitalizations, lowered the use of continuous OCSs and improved control of the disease in these children. Brazil is the largest country in Latin America and has a high prevalence of pediatric asthma and severe disease, particularly in large urban centers . We have recently shown that the burden of asthma in Brazilian children is large, with a high prevalence of the disease (20%), and nearly half of the patients present with uncontrolled disease and a high number of hospitalizations (7.5% of subjects studied in the previous year) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na América Latina a prevalência média atual de sintomas de asma em adolescentes, verificada pela Fase III do International Study of Asthma and Allergies in Childhood (ISAAC) é de 17%, com alta variação entre os países (6,9%-37,6%) [4]. No Brasil, as taxas de prevalência de asma ativa em adolescentes entre 11,8% e 30,5% [5,6].…”
Section: Introductionunclassified